Convergent recruitment of 5'-hydroxylase activities by CYP75B flavonoid B-ring hydroxylases for tricin biosynthesis in Medicago legumes - Lui, Andy C W (The New phytologist, 2020)
© 2020 The Authors. New Phytologist © 2020 New Phytologist Trust.